Focus on wildfires: impacts on health in the context of climate change - Colleen E Reid (IOP Publishing, 2024)
Wildfires are becoming increasingly common in many parts of the world due to a variety of factors including historical fire suppression, increasing drought influenced by climate change, and increasing ignitions from humans. In these regions, wildfire smoke is becoming an increasing source of air pollution people are breathing. Wildfire smoke has been shown to affect numerous physical health outcomes, with clear evidence of impacts on respiratory health but less consistent and comprehensive evidence for effects on cardiovascular disease, mortality, birth outcomes and more. There is a need for more research into which populations are most affected by wildfire smoke; these populations could be affected by where they live and work and how much they are able to protect themselves. Public health interventions that are promoted, such as staying indoors, and using personal air cleaners and masks, may not be equally accessible to all individuals. Additionally, there needs to be research into how best to communicate public health guidance so that it reaches targeted populations. Health impacts from wildfires can also go beyond smoke impacts to include economic and social challenges during recovery when one's home is lost to on-the-job dangers from wildland firefighters. Articles in this focus issue document scientific studies that address some of these topics.